A likeable woman [large type] - Cobb, May, 1973- (Thorndike Press large print high octane, 2023)
"She's back in her affluent hometown for the first time in years and determined to unravel the secrets of her mother's death hidden in the unpublished memoir she left behind--even if it kills her... After her troublemaker mother's mysterious death, Kira fled her wealthy Texas town and never looked back. Now, decades later, Kira is invited to an old frenemy's vow renewal party. Though she is reluctant to go, there are things calling her back... like chilled wine and days spent by the pool... like her sexy childhood crush, Jack. But, more importantly, it's the urgent texts from her grandmother who says she has something to give Kira. Something about her mother's death, something that looks an awful lot like murder. When her grandmother gives Kira a memoir that her mother had been working on before she died, she is pulled into the past and all of the sizzling secrets that come along with it. With few allies left in her gossipy, country club town, Kira turns to Jack for help. As she gets closer to what--and who--might have brought about her mother's end, it becomes clear that someone wants the past to stay buried. And Kira might be next"--